Owners and veterinary surgeons in the United Kingdom disagree about what should happen during a small animal vaccination consultation - Belshaw, Zoe; Robinson, Natalie J.; Dean, Rachel S.; Brennan, Marnie L. (MDPI, 2018)
Dog and cat vaccination consultations are a common part of small animal practice in the United Kingdom. Few data are available describing what happens during those consultations or what participants think about their content. The aim of this novel study was to investigate the attitudes of dog and cat owners and veterinary surgeons towards the content of small animal vaccination consultations. Telephone interviews with veterinary surgeons and pet owners captured rich qualitative data. Thematic analysis was performed to identify key themes. This study reports the theme describing attitudes towards the content of the consultation. Diverse preferences exist for what should be prioritised during vaccination consultations, and mismatched expectations may lead to negative experiences. Vaccination consultations for puppies and kittens were described to have a relatively standardised structure with an educational and preventative healthcare focus. In contrast, adult pet vaccination consultations were described to focus on current physical health problems with only limited discussion of preventative healthcare topics. This first qualitative exploration of UK vaccination consultation expectations suggests that the content and consistency of adult pet vaccination consultations may not meet the needs or expectations of all participants. Redefining preventative healthcare to include all preventable conditions may benefit owners, pets and veterinary surgeons, and may help to provide a clearer structure for adult pet vaccination consultations. This study represents a significant advance our understanding of this consultation type.